Rentier capitalism in the Chilean economy: disconnection between surplus capture and productive investment - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This article examines the structural disconnection between surplus capture and productive investment in the contemporary Chilean economy, contributing empirical evidence to debates on rentier capitalism. Drawing on heterodox political economy, we define rents as persistent surplus profits derived from private control over scarce and strategic assets rather than from value-creating activities. Using firm-level financial data for Chile s largest companies between 2013 and 2023, we identify a systematic concentration of profits among small business groups whose returns consistently exceed sectoral benchmarks, constituting sustained rents. To evaluate whether these rents foster productive upgrading, we complement the firm-level analysis with cross-national evidence on elite investment patterns in Chile and selected Asian economies. Across indicators-private fixed capital formation, R&D spending, and long-term investment-Chile lags significantly behind, suggesting that its accumulation regime is structurally rent-extractive, and weakly oriented toward innovation. Our findings advance research on rentier capitalism by proposing an empirical framework to measure rents and by highlighting the developmental implications of persistent rent extraction in peripheral economies. The article calls for renewed debate on economic elites and the widening disconnection between appropriation and accumulation in the context of current discussions on structural transformation and the future of capitalism in the Global South.